Nutrient management: as a panacea to improve the caryopsis quality and yield potential of durum wheat (Triticum turgidum L.) under the changing climatic conditions - Melash, Anteneh Agezew; Bogale, Amare Assefa; Bytyqi, Bekir; Nyandi, Muhoja Sylivester; Ábrahám, Éva Babett (Frontiers in Plant Science, 2023)
The increasing human population and the changing climate, which have given rise to frequent drought spells, pose a serious threat to global food security, while identification of high-yielding drought-tolerant genotypes coupled with nutrient management remains a proficient approach to cope with these challenges. An increase in seasonal temperature, recurring drought stress, and elevated atmospheric CO2 are alarmingly affecting durum wheat production, productivity, grain quality, and the human systems it supports. An increase in atmospheric carbon dioxide can improve wheat grain yield in a certain amount, but the right amount of nutrients, water, and other required conditions should be met to realize this benefit. Nutrients including nitrogen, silicon, sulfur, and sewage sludge supply could alleviate the adverse effects of abiotic stress by enhancing antioxidant defense and improving nitrogen assimilation, although the effects on plant tolerance to drought stress varied with nitrogen ionic forms. Hence, nutrient management practices offer significant potential to enhance the caryopsis quality and yield the potential for durum wheat. Through implementing tailored nutrient management strategies, farmers, breeders, and agronomists can contribute to sustainable durum wheat production, ensuring food security and maintaining the economic viability of the crop in the face of changing climatic conditions.